Make sustainable manufacturing the heart of the UK's net zero transformation - Jolly, Mark R. (Westminster Publishing Ltd., 2023)
The UK’s net zero future will depend on making things in sustainable ways, with close attention to the whole cycle: the materials we use, the energy and carbon emissions involved in processes, and the opportunities for re-use, re-manufacturing and (last of all) recycling.